"Together We Can": Redefining Work in Nairobi's Urban Transportation Sector. (10th November 2016) - Ference, Meghan
Abstract: Workers in Kenya's informal transportation sector are employed in what anthropologists, sociologists, psychologists, and organizational scholars call "dirty work, " or occupations that are tainted morally, socially, or physically. Although the operators of matatu, minibus taxis, carry a large portion of the Kenya population daily, they face stigmatization and discrimination, which can result in a decrease in lifechances and in some cases even death. In this article, I focus on the outcomes of the occupational stigma that matatu workers experience, and I argue that although the informal transportation workers of Nairobi's matatu sector are stigmatized symbolically and institutionally, they are also increasingly able to contest these perceptions of their work in ways that are having a powerful impact on the workers personally and collectively. The way that workers are reframing the meaning of their labor using a worker‐run union is having an impact on worker identity and sociability leading to an inclusiveness, characteristic of what theorists describe as cosmopolitanism. This process is important for anthropologists to understand as more people are finding work in undesirable and/or informal employment sectors due to the global economic crisis.